Transcranial Magnetic Stimulation in Neuropsychiatry 2018
DOI: 10.5772/intechopen.73218
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive Stimulation of the Cerebellum in Health and Disease

Abstract: The cerebellum is linked to motor, cognitive and affective functions. Anatomically, the cerebellum is part of an interconnected network including a wide range of other brain structures. This chapter reviews ways in which non-invasive stimulation has been used to activate or inhibit these circuits and how this has contributed to our understanding of cerebellar function in both motor and non-motor domains. The utility of non-invasive stimulation of the cerebellum in the treatment of neurological and psychiatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 103 publications
0
5
0
Order By: Relevance
“…Thus, correlational research on the cerebellar contribution to motor learning suggested that the prefrontal cortex and cerebellum work in parallel during acquisition and progression of learning, but they are recruited differently when cognitive and motor demands grow. In accordance, non-invasive stimulation of the cerebellum supports the role of the cerebellum in the initial phase of motor learning (Darch et al, 2018). By contrast, hemicerebellectomy seems to delay the transition to response automatization rather than impair acquisition of sequential learning (Mandolesi et al, 2010).…”
Section: Cerebellar Underpinnings Of Compulsivitymentioning
confidence: 52%
See 1 more Smart Citation
“…Thus, correlational research on the cerebellar contribution to motor learning suggested that the prefrontal cortex and cerebellum work in parallel during acquisition and progression of learning, but they are recruited differently when cognitive and motor demands grow. In accordance, non-invasive stimulation of the cerebellum supports the role of the cerebellum in the initial phase of motor learning (Darch et al, 2018). By contrast, hemicerebellectomy seems to delay the transition to response automatization rather than impair acquisition of sequential learning (Mandolesi et al, 2010).…”
Section: Cerebellar Underpinnings Of Compulsivitymentioning
confidence: 52%
“…Both electrical and non-invasive stimulation of cerebellar activity in animals and humans support a modulatory effect of the cerebellum on cortical activity (Forster and Blaha, 2003; Chen et al, 2014; Watson et al, 2014). It has been hypothesized that the cerebellar modulation consists of what has been called “cerebellar brain inhibitory function” (Darch et al, 2018). If this is the case, one should expect stimulation of cerebellar activity to improve prefrontal functionality and to reduce compulsive and impulsive behaviors (Figure 2).…”
Section: A Working Hypothesis For the Role Of The Cerebellum In Compumentioning
confidence: 99%
“…It has been hypothesized that the cerebellar modulation consists of what has been called “cerebellar brain inhibitory function” ( Darch et al, 2018 ). Patients with posterior cerebellum impairment, particularly in the vermis, show difficulties in controlling their behavior, emotions, and cognitions in what has been called “the cerebellar cognitive-affective syndrome” ( Schmahmann and Sherman, 1998 ).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Consequently, anatomical differences or inadequate electrode/coil placement may lead to heterogenous stimulation of the targeted tissue. Because of the high level of cortical folding in the cerebellum, relative small anatomical interindividual differences may have a greater influence on stimulation responses in the cerebellum compared to other brain regions [210]. Further, recent research has shown that individual factors like the amount of cerebrospinal fluid (CSF) and electrode-to-cortex distance also influence the neurophysiological outcomes of tDCS [211].…”
Section: Challenges and Future Directionsmentioning
confidence: 99%